The Effect of Supplier Collaboration on Company Performance through Lean Manufacture and Inventory Control - Dherma Riofiandi; Zeplin Jiwa Husada Tarigan (Petra International Journal of Business Studies, 2022)
This study examined how supplier collaboration practices can affect company performance through the mediation of lean manufacturing and inventory control in the context of Java, Indonesia. The mediating effect of lean manufacturing and inventory control on the relationship between supplier collaboration practices and company performance was investigated. This survey was collected among 88 manufacturing companies on the island of Java, which are engaged in the chemical and chemical goods sector and the non-metallic minerals industry. Validity and reliability analysis and structural equation modeling to test hypotheses using smartPLS software. This study reveals that supplier collaboration practices positively and significantly affect company performance. In addition, it also found that inventory control positively and significantly mediates the relationship between supplier collaboration practices and company performance. In contrast, lean manufacturing does not significantly mediate the relationship between supplier collaboration practices and company performance. This study contributes to the knowledge of the mediation effect in the practice of inventory control and lean manufacturing on the company performance-supplier collaboration relationship. Company leaders also gain insight on how to collaborate with suppliers to help companies implement more efficient business practices by making continuous improvements and always maintaining inventory levels so that companies can improve their performance.